Development and Validation of a Risk Factor Scoring System for First-Trimester Prediction of Pre-Eclampsia - GOETZINGER, Katherine R. (2014)
OBJECTIVE: To develop a multi-parameter risk-based scoring system for first-trimester prediction of pre-eclampsia and to validate this scoring system in our patient population. STUDY DESIGN: Secondary analysis of a prospective cohort of 1200 patients presenting for first-trimester aneuploidy screening. Maternal serum pregnancy-associated plasma protein A (PAPP-A) levels were measured and bilateral uterine artery (UA) Doppler studies performed. Using the first half of the study population, a prediction model for pre-eclampsia was created. Test performance characteristics were used to determine the optimal score for predicting pre-eclampsia. This model was then validated in the second half of the population. RESULTS: Significant risk factors and their weighted scores derived from the prediction model were chronic hypertension [4], history of pre-eclampsia [3], pre-gestational diabetes [2], body mass index ≥ 30kg/m(2) [2], bilateral UA notching [1], and PAPP-A MoM <10(th) percentile [1]. The AUC for the risk scoring system was 0.76 (95% CI 0. 69–0.83), and the optimal threshold for predicting pre-eclampsia was a total score of ≥6. This AUC did not differ significantly from the AUC observed in our validation cohort [AUC 0.78 (95% CI 0.69–0.86), p=0.75]. CONCLUSION: Our proposed risk factor scoring system demonstrates modest accuracy but excellent reproducibility for first-trimester prediction of pre-eclampsia.